Novel N-Arylmethyl-aniline/chalcone hybrids as potential VEGFR inhibitors: synthesis, biological evaluations, and molecular dynamic simulations - Hesham Haffez; Nosaiba A. Elsayed; Marwa F. Ahmed; Samar S. Fatahala; Eman F. Khaleel; Rehab Mustafa Badi; Eslam B. Elkaeed; Mahmoud A. El Hassab; Sherif F. Hammad; Wagdy M. Eldehna; Nicolas Masurier; Radwan El-Haggar (Taylor & Francis Group, 2023)
Significant advancements have been made in the domain of targeted anticancer therapy for the management of malignancies in recent times. VEGFR-2 is characterised by its pivotal involvement in angiogenesis and subsequent mechanisms that promote tumour cells survival. Herein, novel N-arylmethyl-aniline/chalcone hybrids 5a-5n were designed and synthesised as potential anticancer and VEGFR-2 inhibitors. The anticancer activity was evaluated at the NCI-USA, resulting in the identification of 10 remarkably potent molecules 5a-5j that were further subjected to the five-dose assays. Thereafter, they were explored for their VEGFR-2 inhibitory activity where 5e and 5h emerged as the most potent inhibitors. 5e and 5h induced apoptosis with cell cycle arrest at the SubG0-G1 phase within HCT-116 cells. Moreover, their impact on some key apoptotic genes was assessed, suggesting caspase-dependent apoptosis. Furthermore, molecular docking and molecular dynamics simulations were conducted to explore the binding modes and stability of the protein-ligand complexes.